Suicide in the elderly 60 years of age and over in the south-east part of Serbia - Petrovic, B; Kocic, B; Bašic, S; Jovanovic, J; Jovic, S; Arandelovic, M; Tasic, S (Central European Journal of Public Health, 2004)
Some previous investigations indicated that economic crisis (inflation in Serbia 1993/94) have great influence on increasing suicide rates in Serbia. After that suicide decreased, despite the war and bombing in 1999, specially among the elderly people. A total of 453 suicides were registered on the territory of south-eastern Serbia during 1995-2001 years. Of them 295 (65.1%) were aged over 60 years. Generally, linear trends of suicide among both genders from 1995 to 2001 decreased, but the slope of decreasing was grater among males than among females. The highest rates among the both genders were registered in the years with the maximum number of suicides, but the linear trends of rates have statistically important correlation with time (r > 0.5). Average annual suicide rate among males was 42.5, and among women it was 18.7. The highest average annual suicide rate among men was observed in the age group 75 years and over (93.3) , and the lowest in the age group 65-69 (20.6). Among males, in the all age group linear trends of suicide rates decreased, with the highest slope among 75 years and over and the lowest among 65-69 years. The highest suicide rate among females was registered in age group 75 years and over (25.6), the lowest in the age group 65-69 (13.5). The linear trends are similar as among males: downward trend was observed among all aged groups, with the highest slope among women 75 years and over. The most common way of suicide among men was hanging up (63%), poisoning and by firearms. There were no statistical differences between way of suicide and age groups. The most frequent way of suicide among females was hanging up (55%), poisoning (25%) and drowning (12%). There were statistically significant differences in drowning between age groups, 70-74 and 75 and over (p<0.05), and between poisoning and age groups 60-64 years and 75 years and over. Poisoning and drowning are statistically more frequent among women than among men.
Keywords: Socioeconomic Factors; Male; statistika přirozeného pohybu; Yugoslavia; Adult; Age Factors; socioekonomické faktory; Aged; sebevražda; dospělí; mužské pohlaví; senioři; Vital Statistics; lidé; Suicide; ženské pohlaví; Humans; věkové faktory; Jugoslávie; Female